Application of Global Lung Function Initiative Global Spirometry Reference Equations across a Large, Multicenter Pulmonary Function Lab Population - Kanj, Amjad N.; Scanlon, Paul D.; Yadav, Hemang; Smith, William T.; Herzog, Tyler L.; Bungum, Aaron; Poliszuk, Daniel; Fick, Edward; Lee, Augustine S.; Niven, Alexander S. (American journal of respiratory and critical care medicine, 2024)
Global Lung Function Initiative (GLI) Global spirometry reference equations were recently derived to offer a "race-neutral" interpretation option. The impact of transitioning from the race-specific GLI-2012 to the GLI Global reference equations is unknown. Describe the direction and magnitude of changes in predicted lung function measurements in a population of diverse race and ethnicity using GLI Global in place of GLI-2012 reference equations. In this multicenter cross-sectional study using a large pulmonary function laboratory database, 109,447 spirometry tests were reanalyzed using GLI Global reference equations and compared with the existing GLI-2012 standard, stratified by self-reported race and ethnicity. Mean FEV and FVC percent predicted increased in the White and Northeast Asian groups and decreased in the Black, Southeast Asian, and mixed/other race groups. The prevalence of obstruction increased by 9.7% in the White group, and prevalences of possible restriction increased by 51.1% and 37.1% in the Black and Southeast Asian groups, respectively. Using GLI Global in a population with equal representation of all five race and ethnicity groups altered the interpretation category for 10.2% of spirometry tests. Subjects who self-identified as Black were the only group with a relative increase in the frequency of abnormal spirometry test results (32.9%). The use of GLI Global reference equations will significantly impact spirometry interpretation. Although GLI Global offers an innovative approach to transition from race-specific reference equations, it is important to recognize the continued need to place these data within an appropriate clinical context.